State labor legislation enacted in 1997. - Nelson, Richard R. (Monthly Labor Review, 1998)
A greater amount of state legislation was enacted in 1997 than in previous years. Laws of major significance were introduced in a number of employment standards areas, including the usual fields of minimum wage protection, prevailing wage, and child labor, and in newer areas of parental leave, immunity from liability for providing job information, restrictions on drug and alcohol testing, and prohibitions on employment discrimination based on sexual orientation or genetic testing. In addition, some important court decisions were made during the year that affected employment standards laws. The writer provides a summary, by jurisdiction, of significant state labor legislation enacted in 1997.